DEMOKRASI PENDIDIKAN OLEH JOHN DEWEY DAN RELEVANSINYA DENGAN PENDIDIKAN ANAK USIA DINI: Demokrasi Pendidikan Anak Usia Dini - Ulfa Ainul Mardhiyah (LP3M Sekolah Tinggi Agama Islam Ma'arif Magetan, 2020)
John is one of the figures who tries to after a system with the aim of improving the quality of the education process and covering the short coming of the world of education,namely educational democracy. John Dewey emphasired the importance of realizing a democracie school. In this regard the author tries to analyze the concept of educational democracy raised by John Dewey and its relevance to early childhood education. This type of research is literature research the method of data analysis in this study is description analysis. In this study it was found that the concept the John Dewey is relevant to the condition of early chilhood. Where children need dyrect experience with the learning by doing method. Whit is focused on student activity. Criticism of the concept John Dewey education still ignores the natula of faith in every student. Where as in the early chilhood stage this character education is needed to strengthen and take care of nature and as a routed foundation through positive imagination and love inthe family and the imediate environment.